Mitigating Food waste through Sustainable Supply Chains - Usama, Muhammad (2019)
A structured literature review has been performed in this research to identify the reasons for the food waste in the supply chain and potential measures have been suggested for mitigating the waste. The research also identifies the key challenges faced by the food supply chains. The research reveals that food is wasted at not only at one stage but at every stage starting from harvesting till final consumption. All the supply chain actors play a significant role in generating waste and external factors including environmental conditions and regulatory implications makes the further situation even more worse. The literature shows that this issue of food waste is new and therefore a limited literature is available on this topic and several authors have conflicts on the ways of calculating or estimating waste and until now there is no consensus regarding the definition of food waste. Lastly, the limitations have been pointed out and further research has been proposed